The role of personality as moderator in the relationship of parental involvement and career indecision among Indonesian adolescents - Siti Rezeki Emelia; Koernialis, Ichsan; Latipun, Latipun (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study aims to determine the role of personality dimensions in the relationship of parental involvement on career indecision. The study was conducted on high school students (N = 129) 16 - 18 years old (M = 16.47 SD = 0.573). Three instruments used in data collection are Parental Career-Related Behavior, Career Decision Scale, and IPIPBig Five Personality. Regression Analysis and Process v3.4 Hayes with the help of the SPSS 21 program. The results of the study showed a significant relationship between parental involvement and career indecision moderated by agreeableness, conscientiousness and neuroticism personality. Extraversion and openness to experience personality are not significant as moderating variables of parental involvement and career indecision.